Preparation and bioactive properties of chitosan and casein phosphopeptides composite coatings for orthopedic implants. (20th November 2015) - Qin, Liguo; Dong, Huanhuan; Mu, Ziqing; Zhang, Yali; Dong, Guangneng
Highlights: CPP was immobilized to Co–Cr–Mo alloy after CS was covalently bound to substrate. The CS/CPP films can significantly increase the proliferation of MC3T3-E1 cells. BMP-2 mRNA on cells cultured on CS/CPP films was increased 5-fold. OPG/RNAKL mRNA on cells cultured on CS/CPP films was increased 55-fold. CS/CPP coatings formed by the layer-by-layer method are highly bioactive. Abstract: Using the layer-by-layer deposition method, functional chitosan/casein phospopeptides (CS/CPP) composite coatings were produced on Co–Cr–Mo alloy. The CS/CPP composite coatings had the dendritic topography, and were quite hydrophilic. Zeta potential measurements showed the composite coatings were negative charged at neural pH. XPS results indicated that the CS/CPP composite coatings were covalently bond to the substrate. When MC3T3-E1 cells were seeded on the CS/CPP composite coatings, no cytotoxicity was observed. The bone morphogenetic protein-2 (BMP-2) mRNA expression was significantly up-regulated in MC3T3-E1 cells cultured on the composite coatings and it was twice as much as that of cells cultured on the bare substrate. The expression of osteoprotegerin (OPG) mRNA and the ratio of OPG/receptor activator of nuclear factor-κB ligand (RNAKL) mRNA were increased 5-fold and 55-fold, respectively. These results suggested the CS/CPP composite coatings may have potential application in cobalt matrix orthopaedic implants.